Characterization of the Theta to Beta Ratio in ADHD: Identifying Potential Sources of Heterogeneity. (July 2013) - Loo, Sandra K.; Cho, Alexander; Hale, T. Sigi; McGough, James; McCracken, James; Smalley, Susan L.
Objective: The goal of this study is to characterize the theta to beta ratio (THBR) obtained from electroencephalogram (EEG) measures, in a large sample of community and clinical participants with regard to (a) ADHD diagnosis and subtypes, (b) common psychiatric comorbidities, and (c) cognitive correlates.Method: The sample includes 871 participants (595 youth and 276 adults) with and without ADHD. All participants underwent extensive assessment, including semistructured diagnostic interviews, cognitive testing, and EEG recording.Results: The THBR did not differ significantly by ADHD status for youth but was significantly lower in adults with ADHD compared with controls. ADHD subtype and psychiatric comorbidities such as disruptive behavior disorders and depression have opposing and significant mediating effects on the THBR.Conclusion: The THBR is affected by several mediating factors associated with ADHD such as ADHD subtype and psychiatric comorbidity. More research is needed to understand the functional significance of the THBR in ADHD.